Impact of Chronic Kidney Disease on the Outcomes of Patients Undergoing Left Atrial Appendage Occlusion: Insights from a Large National Database - Rivera, Frederick Berro (Archīum Ateneo, 2024)
Introduction Studies exploring the effectiveness and safety of left atrial appendage occlusion (LAAO) in patients with chronic kidney disease (CKD) are limited. Methods We utilized the National Inpatient Sample (NIS) to identify hospitalizations for LAAO from 2016 to 2020 and further identified cases with concomitant CKD. The primary outcome was mortality, and secondary outcomes were cerebrovascular accidents, major bleeding, vasopressor requirements, percutaneous coronary intervention, cardiac arrest, acute respiratory failure, transfusion, length of stay (LOS), and total hospital charges. Multivariable logistic regression was performed to further adjust for covariates. Results A total of 89,309 LAAO procedures from 2016 to 2020 were identified, of which 21,559 (24.1%) reported concomitant CKD, with males comprising the majority (62.2%). An increasing trend in LAAO procedures was seen from 2.24 to 13.9 per 10,000 patients from 2016 to 2020. Despite patients with CKD having a higher rate of most comorbidities, there was no difference in mortality (non-CKD vs. CKD, 0.07% vs. 0.42%; aOR: 1.3, 95% CI: 0.4-4.4, p = 0.686) and complications for CKD and non-CKD patients, while CKD patients had longer LOS and higher total hospital charge. No significant sex differences in outcomes among CKD patients were observed except for a longer LOS in females. Conclusion Despite generally having more comorbidities, outcomes of patients with CKD following LAAO are similar to those without CKD, suggesting that LAAO can be offered as a safe option for the treatment of atrial fibrillation in eligible patients with CKD.